Age-related brain atrophy may be mitigated by internal jugular vein enlargement in male individuals without neurologic disease. (March 2017) - Belov, Pavel; Magnano, Christopher; Krawiecki, Jacqueline; Hagemeier, Jesper; Bergsland, Niels; Beggs, Clive; Zivadinov, Robert
Objectives: To assess the relationship between cross-sectional area of internal jugular veins and brain volumes in healthy individuals without neurologic disease. Methods: A total of 193 healthy individuals without neurologic disease (63 male and 130 female; age > 20 to < 70 years) received magnetic resonance venography and structural brain magnetic resonance imaging at 3T. The internal jugular vein cross-sectional area was assessed at C2–C3, C4, C5–C6, and C7–T1. Normalized whole brain volume was assessed. Partial correlation analyses were used to determine associations. Results: There was an inverse relationship between normalized whole brain volume and total internal jugular vein cross-sectional area (C7–T1: males r = −0.346, p = 0.029; females r = −0.301, p = 0.002). After age adjustment, association of normalized whole brain volume and normalized gray matter volume with internal jugular vein cross-sectional area became positive in males (normalized whole brain volume and right internal jugular vein cross-sectional area (C2–C3) changed from r = −0.163 to r = 0.384, p = 0.002), but not in the females. Conclusion: Sex differences exist in the relationship between brain volume and internal jugular vein cross-sectional area in healthy individuals without neurologic disease.